2019
DOI: 10.12968/hmed.2019.80.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Overview of eosinophilic oesophagitis

Stephen E Attwood

Abstract: The most specific and indicative symptom of eosinophilic oesophagitis is a feeling of food sticking in the chest after swallowing (Attwood et al, 1993; Straumann et al, 1994). Sometimes it is just a feeling of the food moving slowly, in other patients it clearly feels as if food sticks for a while and in some the sticking of a food bolus continues for a long time. Patients may have intermittent symptoms but in many dysphagia is present all the time, albeit in varying degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
0
9
0
7
Order By: Relevance
“…La EEo es una entidad clínico patológica conocida entre los pacientes pediátricos y adultos que acuden a los servicios de alergia y gastroenterología de todo el mundo (2). De hecho, la mayoría de los pacientes presentan manifestaciones de sensibilización a los alérgenos alimentarios y a aeroalérgenos, definida por las pruebas de inyección cutánea y/o por la IgE específica del alérgeno, no obstante, solo una minoría refieren antecedente de anafilaxia alimentaria (7). La creciente prevalencia de EEo ha centrado la atención en las exposiciones ambientales.…”
Section: Etiopatogeniaunclassified
See 3 more Smart Citations
“…La EEo es una entidad clínico patológica conocida entre los pacientes pediátricos y adultos que acuden a los servicios de alergia y gastroenterología de todo el mundo (2). De hecho, la mayoría de los pacientes presentan manifestaciones de sensibilización a los alérgenos alimentarios y a aeroalérgenos, definida por las pruebas de inyección cutánea y/o por la IgE específica del alérgeno, no obstante, solo una minoría refieren antecedente de anafilaxia alimentaria (7). La creciente prevalencia de EEo ha centrado la atención en las exposiciones ambientales.…”
Section: Etiopatogeniaunclassified
“…5 (2), Febrero 2020 -ISSN:2215-4523 / e-ISSN:2215-5279 http://revistamedicasinergia.com crecimiento tisular beta (TGF-B), producido por los eosinófilos y mastocitos, también contribuye a la remodelación tisular y la disfunción del músculo liso. El gen más sobreexpresado por los pacientes con EEo, fue la eotaxina 3, y su cantidad se correlaciona con la gravedad de la enfermedad (1,7).…”
Section: Etiopatogeniaunclassified
See 2 more Smart Citations
“…Exposure to luminal contents is key to other oesophageal diseases, notably eosinophilic oesophagitis. Exposure to ingested food allergens (in the vast majority) results in eosinophilic infiltrate in the mucosa (and frequently deeper layers) in affected individuals, with dysphagia being the predominant symptom 9 . Some investigators have suggested that acid reflux, and its subsequent impact on mucosal integrity, may play a role in eosinophilic oesophagitis pathogenesis 10 …”
Section: Introductionmentioning
confidence: 99%